Pendidikan Pemahaman Islam Nusantara - Surawardi Surawardi (STAI AL FALAH Banjarbaru, 2021)
The emergence of the term Islam Nusantara invites many pros and cons from the community, including from academics. Islam that was revealed is Islam for all Muslims everywhere from this hemisphere. If it is labelled as Nusantara, it will give the impression of a partial understanding of Islam from among the Muslims themselves. There is nothing wrong with the term